2008
DOI: 10.1007/s00192-008-0603-1
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor alpha polymorphism is associated with pelvic organ prolapse risk

Abstract: Estrogen and estrogen receptors are known to play important roles in the pathophysiology of pelvic organ prolapse (POP). We investigated whether estrogen receptor alpha (ERalpha) gene polymorphisms were associated with POP risk by conducting a case-control association study in 88 women with POP and 153 women without POP. Genotypes of the ERalpha (ESR1) gene polymorphisms (rs17847075, rs2207647, rs2234693, rs3798577, and rs2228480) were determined by polymerase chain reaction, followed by restriction fragment l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Of these articles, 21 pertained to the genetic epidemiology of POP (Figure 1). This included one GWAS(17), two linkage analyses(18,19) and 18 case-control candidate gene association studies(2037) involving 10 candidate genes (collagen type 1 alpha 1 ( COL1A1 ) (n=5)(2628,33,35), collagen type 3 alpha 1 ( COL3A1 ) (n=4)(20,3032), laminin gamma-1 ( LAMC1 ) (n=3) (19,23,36), matrix metalloproteinase 9 ( MMP9 ) (n=3)(24,28,37), matrix metalloproteinases 1 and 3 ( MMP1 & 3 ) (n=2)(28,34), lysyl oxidase-like 1 ( LOXL1 ) (n=1)(29), estrogen receptor alpha ( ER α)(n=1)(21), estrogen receptor beta ( ER β)(n=1)(22), progesterone receptor (PGR) (n=1)(25) (Table 1). All studies were published in 2007 or later.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these articles, 21 pertained to the genetic epidemiology of POP (Figure 1). This included one GWAS(17), two linkage analyses(18,19) and 18 case-control candidate gene association studies(2037) involving 10 candidate genes (collagen type 1 alpha 1 ( COL1A1 ) (n=5)(2628,33,35), collagen type 3 alpha 1 ( COL3A1 ) (n=4)(20,3032), laminin gamma-1 ( LAMC1 ) (n=3) (19,23,36), matrix metalloproteinase 9 ( MMP9 ) (n=3)(24,28,37), matrix metalloproteinases 1 and 3 ( MMP1 & 3 ) (n=2)(28,34), lysyl oxidase-like 1 ( LOXL1 ) (n=1)(29), estrogen receptor alpha ( ER α)(n=1)(21), estrogen receptor beta ( ER β)(n=1)(22), progesterone receptor (PGR) (n=1)(25) (Table 1). All studies were published in 2007 or later.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were published in 2007 or later. Most had government(17,18,20,21,23,25,29,3237) and/or university grant funding(2022,24,25), 71% (15/21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that polymorphisms in the ERα gene are associated with an increased risk of POP [18], and many studies have indicated that reduced ERα expression occurs in POP [12,13]; however, the mechanisms that regulate reduced ERα protein levels are not known. This study confirms the previous studies of reduced ER expression in POP [12,13], as we observed that ERα protein is also downregulated in the cervical portion of the uterosacral ligament of POP patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that annual POP surgeries involve an expenditure of over USD 1 billion [2]. The etiologies of POP have been extensively reviewed [5,6,7,8], and current evidence suggests an important etiology of POP is the degradation of collagen in vaginal tissues [9,10]. Interestingly, strengthening collagen fibers by cross-linking in collagen types I, III and V has been achieved using combined riboflavin UVA (365-370 nm) photoactivation treatment in corneal repairs [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%